Digital workflow to improve osteoarchaeological documentation. (June 2019) - Valente, Riccardo
Abstract: This paper presents a feasible method mainly based on digital photogrammetry and digital modelling to obtain a more complete documentation of skeletal remains excavated during archaeological investigations. Osteoarchaeological analysis and methods are crucial when a large number of human remains is individuated, and the related documentation needs to be as accurate as possible. The presented workflow allows for obtaining several outputs (orthoimages, vector drawings, 3D models) that can be successfully used as support for osteoarchaeologists in both in-field and post-excavation activities. Digital photogrammetry allows one to speed up the recording phase during fieldwork. However, the digital representation of skeletal remains is open to further interpretations of funerary contexts. Highlights: A method for obtaining 3D representations of skeletal remains discovered in archaeological contexts is presented. Digital photogrammetry is used to collect in-field datasets. The results can help osteoarchaeologists in recording and analysing ancient skeletal remains in an innovative way.